PENGARUH ONLINE CUSTOMER REVIEW TERHADAP KEPUTUSAN PEMBELIAN PRODUK DHINDA HIJAB - Khoirunnisa, Khoirunnisa; Yusuf, Abdul (Jurnal Manajemen dan Bisnis, 2025)
This study aims to evaluate the influence of online customer reviews on the purchasing decisions of Dhinda Hijab products. In the current digital era, consumers increasingly rely on online reviews from other users before making purchasing decisions. Online customer reviews are considered credible sources of information and can reduce perceived risks for consumers when making online purchases. The research method employed is a quantitative approach, distributing questionnaires to Dhinda Hijab consumers who have read online customer reviews. Data analysis is conducted using simple linear regression to test hypotheses and assess the impact of the online customer review variable on purchasing decisions. The results indicate that online customer reviews have a positive and significant influence on purchasing decisions for Dhinda Hijab products. The better and more credible the online customer reviews, the higher the level of consumer purchasing decisions for Dhinda Hijab products